Prospective controlled evaluation of the effect of a community based asthma education centre in a multiracial working class neighbourhood. Issue 10 (October 1994) - Garrett, J; Fenwick, J M; Taylor, G; Mitchell, E; Stewart, J; Rea, H
Abstract : BACKGROUND–Previous work has indicated a high rate of non-attendance at hospital based clinics among young, multiracial asthmatic patients of lower socioeconomic class. The efficacy of delivering asthma education from a community health centre established in a multiracial working class neighbourhood was evaluated. METHODS–A prospective controlled study was performed in which asthmatic subjects aged between two and 55 years attending a hospital emergency room with acute asthma and living within a defined geographical area of high emergency room users were randomised to the usual follow up or the education centre plus usual follow up. Measurements were taken at entry into the study and again nine months later. RESULTS–At nine months patients randomised to the education centre had more preventive medications, more peak expiratory flow meters and better flow meter technique, more self-management plans, better knowledge of appropriate action to take when confronted with worsening asthma, less nocturnal awakening, and better self-reported asthma control than the control group. There was no difference between the study groups in measurements of compliance, hospital admission, days lost from school or work, or emergency room use. CONCLUSIONS–The main effects of education were on asthma knowledge and self-management skills, whilst improvements in asthma morbidity were small. Potential reasons for this include heterogeneous study population (in terms of baseline self-management skills, asthma severity, ethnicity and age), pragmatic study design, insensitivity of many of the measurements of morbidity, the modest effectiveness of a single time limited education programme, and inability to limit the effects of such a large community based study to the intervention group (there was a 67% reduction in asthma admissions during the study period from the geographical area targeted compared with a 22% reduction for the rest of Auckland).